Biomechanical analysis of the plantar and upper pressure with different sports shoes. (1st January 2014) - Mei, Qichang; Graham, Michael; Gu, Yaodong
The purpose of the study is to probe into the difference in plantar pressure and dorsal pressure of three types of sports shoes: Basketball Shoes (BS); Running Shoes (RS); Tennis Shoes (TS). The novel insole measurement system and pressure sensor chips are utilised to obtain plantar and dorsal pressure. As to dorsal pressure, maximal Lateral Metatarsophalangeal (LM) joint of TS is distinctively different from BS and RS, mean LM of RS is apparently distinct from BS and TS. These distinctions might be of importance while designing shoes; factors like athletic performance, perceived comfort and injury prevention should be taken into consideration.